2021
DOI: 10.1007/s11538-021-00864-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Signaling Circuit with Dual Species of GTPase Switches

Abstract: GTPases are molecular switches that regulate a wide range of cellular processes, such as organelle biogenesis, position, shape, and function, vesicular transport between organelles, and signal transduction. These hydrolase enzymes operate by toggling between an active "ON") guanosine triphosphate (GTP)-bound state and an inactive ("OFF") guanosine diphosphate (GDP)-bound state; such a toggle is regulated by GEFs (guanine nucleotide exchange factors) and GAPs (GTPase activating proteins).Here we propose a model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…The net result of this is that the closed loop feedback control allows for a tighter alignment of secretion with respect to EGF by ‘stretching’ out the dose-response curve across series of switches to propagate the signal from the extracellular space to the interior of the cell. Because the stability behavior of a mathematically simpler version of this closed loop system of coupled GTPases showed that coupling afforded a wide range of steady states (Stolerman et al, 2021), it is tempting to speculate that the coupled system allows flexibility in responses over a wide range of stimulus. In fact, follow-up work has now revealed how ranges of activity of the mGTPase Arf1, reaction kinetics, the negative feedback loop (mGAP), and the cascade length affect DoRA (Qiao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The net result of this is that the closed loop feedback control allows for a tighter alignment of secretion with respect to EGF by ‘stretching’ out the dose-response curve across series of switches to propagate the signal from the extracellular space to the interior of the cell. Because the stability behavior of a mathematically simpler version of this closed loop system of coupled GTPases showed that coupling afforded a wide range of steady states (Stolerman et al, 2021), it is tempting to speculate that the coupled system allows flexibility in responses over a wide range of stimulus. In fact, follow-up work has now revealed how ranges of activity of the mGTPase Arf1, reaction kinetics, the negative feedback loop (mGAP), and the cascade length affect DoRA (Qiao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…1c). In the presence of epidermal growth factor (EGF), the active Ras-superfamily mGTPases Arf1 on Golgi membrane recruit GIV/Girdin (a protein that is known to fuel aggressive traits in diverse cancers), and the latter works as guanine nucleotide exchange factor (GEF) to turn tGTPases Giαβγ on [41][42][43][44][45] . Subsequently, GIV increases the level of the GAP for mGTPase by molecular scaffolding action, and the activated tGTPase acts as a co-factor to maximally activate the GAP.…”
Section: Model Developmentmentioning
confidence: 99%
“…Subsequently, GIV increases the level of the GAP for mGTPase by molecular scaffolding action, and the activated tGTPase acts as a co-factor to maximally activate the GAP. This circuit was subsequently modeled for cell secretion 34 and for stability analysis 45 .…”
Section: Model Developmentmentioning
confidence: 99%
“…We briefly describe the biochemical circuit that we study here; this circuit was originally described in mammalian cells and experimentally interrogated in (33), (Figure 1A). In the presence of epider mal growth factor (EGF), the active Rassuperfamily mGTPases Arf1 on Golgi membrane recruit GIV/Girdin (a protein that is known to fuel aggressive traits in diverse cancers), and the latter works as guanine nucleotide exchange factor (GEF) to turn tGTPases Gi on (39)(40)(41)(42)(43). Subsequently, GIV increases the level of the GAP for mGTPase by molecular scaffolding action, and the activated tGT Pase acts as a cofactor to maximally activate the GAP.…”
Section: Model Developmentmentioning
confidence: 99%
“…Subsequently, GIV increases the level of the GAP for mGTPase by molecular scaffolding action, and the activated tGT-Pase acts as a co-factor to maximally activate the GAP. This circuit was subsequently modeled for cell secretion (44) and for stability analysis (43).…”
Section: Model Developmentmentioning
confidence: 99%